Accessing 3D Location of Standing Pelvis: Relative Position of Sacral Plateau and Acetabular Cavities versus Pelvis - E. Berthonnaud; R. Hilmi; J. Dimnet (Radiology Research and Practice)
The goal of this paper is to access to pelvis position and morphology in standing posture and to determine the relative locations of their articular surfaces. This is obtained from coupling biplanar radiography and bone modeling. The technique involves different successive steps. Punctual landmarks are first reconstructed, in space, from their projected images, identified on two orthogonal standing X-rays. Geometric models, of global pelvis and articular surfaces, are determined from punctual landmarks. The global pelvis is represented as a triangle of summits: the two femoral head centers and the sacral plateau center. The two acetabular cavities are modeled as hemispheres. The anterior sacral plateau edge is represented by an hemi-ellipsis. The modeled articular surfaces are projected on each X-ray. Their optimal location is obtained when the projected contours of their models best fit real outlines identified from landmark images. Linear and angular parameters characterizing the position of global pelvis and articular surfaces are calculated from the corresponding sets of axis. Relative positions of sacral plateau, and acetabular cavities, are then calculated. Two hundred standing pelvis, of subjects and scoliotic patients, have been studied. Examples are presented. They focus upon pelvis orientations, relative positions of articular surfaces, and pelvis asymmetries.